2023
DOI: 10.5603/ep.a2023.0026
|View full text |Cite
|
Sign up to set email alerts
|

Galanin-like peptide and its correlation with androgen levels in patients with polycystic ovary syndrome

Abstract: gonadotrophin-releasing hormone (GnRH), leading to increased amplitude and frequency of luteinizing hormone (LH) secretion and stimulation of theca cells to produce androgen; decreased levels of follicle-stimulating hormone (FSH) relative to LH, insulin resistance in adipose tissue and skeletal muscles via a post-receptor defect (abnormal phosphorylation of tyrosine kinase), pancreatic beta-cell dysfunction, and obesity [4][5][6].The elevated LH pulse frequency, increased hypothalamic kisspeptin levels, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Several investigations revealed a similar conclusion. 16-18 Others, however, found that women with PCOS had higher levels of D-dimer than a healthy control group. 11,19,20 Higher D-dimer levels suggest increased subclinical fibrin synthesis rather than a breakdown in the setting of decreased global fibrinolytic activity.…”
Section: Discussionmentioning
confidence: 98%
“…Several investigations revealed a similar conclusion. 16-18 Others, however, found that women with PCOS had higher levels of D-dimer than a healthy control group. 11,19,20 Higher D-dimer levels suggest increased subclinical fibrin synthesis rather than a breakdown in the setting of decreased global fibrinolytic activity.…”
Section: Discussionmentioning
confidence: 98%